Financial Literacy and Budgeting Behavior of University Teachers in Nepal: The Moderating Role of Financial Attitude - Subedi, Dhruba Prasad; Gyawali, Achyut (Nepal Journal of Multidisciplinary Research, 2025)
Background: Effective personal financial management has emerged as a vital life skill in the context of a financial environment. This is particularly important for university teachers, who not only manage their own finances but also serve as role models within society. Even though it is commonly acknowledged that financial literacy is a major factor in encouraging practical financial behavior to develop financial attitude especially in developing nations like Nepal. Methods: Using a structured questionnaire and a quantitative research design, this study examined the relationship between budgeting behavior, financial attitude, and financial literacy. 250 university teachers from various Nepalese academic institutions provided the data. The proposed relationships were tested through statistical analysis, including moderation analysis. Results: The findings of the study show a strong positive relationship between financial literacy and budgeting behavior. Financial attitude also has a significant positive effect on budgeting behavior. Notably, financial attitude significantly influences the relationship between financial literacy and budgeting behavior. It enhances the positive impact of financial literacy when a good financial attitude exists. Conclusion: Both knowledge and attitude are important for university teachers in Nepal follow good budgeting habits. Simply improving financial literacy may not be enough if it isn’t supported by a positive attitude toward finances. So, financial education programs should take a more complete approach by focusing on both teaching financial skills and shaping a healthy mindset about money. Novelty: This study is one of the first to look at how financial attitude affects the relationship between financial literacy and budgeting behavior in the Nepalese higher education sector. It offers new insights into the importance of both knowledge and attitude in encouraging good financial habits, especially in a developing country.